Aktivitas Antiinflamasi Ekstrak Kayu Bajakah (Spatholobus littoralis Hask): Anti-inflammatory Activity of Bajakah Wood Extract (Spatholobus littoralis Hask) - Nastiti, Kunti; Nugraha, Dyan Fitri (Jurnal Surya Medika (JSM), 2022)
Bajakah wood (Spatholobus littoralis Hassk) is a native plant of Kalimantan which is widely used by the community to treat diarrhea, dysentery, aches, and pains, wound medicine and is even believed to be a cancer drug. Research on this plant is still very limited. The content of flavonoids is thought to act as an anti-inflammatory. The purpose of this study was to determine the effectiveness of Kayu Bajakah (Spatholobus littoralis Hassk) as an anti-inflammatory in male rats induced by carrageenin. The method used in this study was an experimental method using 21 male white rats aged 2-3 months weighing 150-250 grams which were divided into 7 groups, namely the normal group, the CMC Na group, the diclofenac sodium group 1.35 mg/day. 200 g BW and 4 doses of Kayu Bajakah ethanol extract: 50, 100, 200, and 400 mg/kg BW orally. Fifteen minutes after treatment, mice were injected with 1% carrageenin subplantar. The volume of edema was measured with a plestimometer every 60 minutes for 4 hours. Anti-inflammatory was measured by comparing the percentage value of edema inhibition in the control and treatment groups. The results showed that the four treatment groups had a significantly different total volume of edema at 240’ minutes with a significance value less than 0.05. The greatest anti-inflammatory effect was at a dose of 400 mg/kg BW at the 240th minute with a percentage of 87.65%. Kayu Bajakah (Spatholobus littoralis Hassk) ethanol extract has anti-inflammatory activity.